Public Policy Making, Gender, and Human Security in the Caribbean - Mc Fee, Deborah N.; Rogers, Tracie A. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2025)
XLVII, 440 p. 30 illus., 25 illus. in color.